"Minima Origeniana": questioni linguistico-testuali e citazioni dei "Proverbi" nel 'Nuovo Origene' - Neri, Camillo (Adamantius, 2016)
"This is the first of three contributions in which the recent edition of Origen's "Homilies on the Psalms" and their cultural significance are discussed ..."